Praktik Kafa’ah pada Perkawinan Anggota Lembaga Dakwah Islam Indonesia di Kabupaten Wonogiri - Firdaus, Royan Ahila; Ridho, Muhammad Rosyid (Prodi Hukum Ekonomi Syariah (Muamalah), 2024)
Lembaga Dakwah Islam Indonesia (LDII) Wonogiri Regency has different views regarding kafa'ah both in theory and implementation. theory and implementation. The type of research is qualitative, using a field study approach. Data collection techniques through observation, documentation, and interviews with primary and secondary sources. primary and secondary sources. Data analysis was carried out by means of reduction, presentation, and conclusion drawing. The results show that the practice of kafa'ah practice implemented by members of LDII Wonogiri Regency although it is not an absolute an obligation, but it remains the focus of attention that is always implemented by each member. Implemented by each of its members. A marriage will be easier to realise to be realised because they already understand each other's backgrounds so that in realising a harmonious family and avoiding conflicts that risk a split in the household.